Trend Research of Problem-Based Learning to Improve Students' Science Process Skills: Article Review - Maulidatin Nanisfi; Susilawati Susilawati; Gunawan Gunawan; Agil Al Idrus; A A Sukarso (Current Educational Review, 2025)
Problem-based learning (PBL) has been recognized as one of the effective teaching methods for improving students' critical thinking and problem-solving skills. This article aims to analyze research trends related to PBL in the context of improving students' science process skills. This study uses a bibliometric analysis method, with data taken from Google Scholar from 2015-2024 with the help of Publish or Perish, Dimensions.ai., and VOSviewer apps. The results of the analysis show that the number of documents with PBL topics and student science processes skill increased steadily from 2014-2023, and decreased slightly in 2024 (until October 18, 2024). This research also highlights the importance of integrating PBL with the Science, Technology, Engineering, and Mathematics (STEM) approach and the use of technology for 21st-century skill development. Furthermore, this study recommends that future research focus more on topics that are still less explored, such as local wisdom and inquiry approaches in science learning